(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
One way to increase tourist visits to a tourist destination is to increase the interest of tourists to visit which can be influenced by social media marketing, tourist facilities, and the image of the destination. The purpose of this study was to determine the effect of social media marketing, tourist facilities, and the image of the destination on the interest of visiting tourists. This research was conducted at Ceking Rice Terrace Tegallalang with a population of 8,778,448 visitors in 2020 and a sample of 100 visitors using the slovin formula and accidental sampling technique. Data was collected by means of interviews and questionnaires as measured by a Likert scale of five answer choices. The instrument test was carried out by testing the validity and reliability testing followed by classical assumptions and multiple linear regression analysis to test the hypothesis. The results of the analysis prove that social media marketing, tourist facilities, and the image of the destination have a positive and significant effect on the interest of visiting tourists.